2014
DOI: 10.1002/cam4.232
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+‐activated Cl channel, ANO1 (TMEM16A), is a double‐edged sword in cell proliferation and tumorigenesis

Abstract: Since anoctamin 1 ANO1 (TMEM16A) was found to be a molecular component of Ca2+-activated Cl− channels, its role in tumorigenesis has gained attention at a fast pace. ANO1 overexpression frequently occurs in the cancer tissues along with 11q13 chromosome amplification. Poor prognosis of many types of cancers has been closely correlated with ANO1 gene amplification and protein overexpression. ANO1 is now considered an excellent biomarker for certain cancers. Recent research suggests that it is the channel functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 61 publications
1
59
1
3
Order By: Relevance
“…Outside of the GI tract, Ano1 is present in the vascular smooth muscle (3,36), salivary glands, thyroid, pancreas, prostate, and urinary and gall bladders (29). 11q13 chromosome amplification and subsequent Ano1 overexpression are indicators of poor prognosis for a variety of tumors (1,19,27,40).…”
mentioning
confidence: 99%
“…Outside of the GI tract, Ano1 is present in the vascular smooth muscle (3,36), salivary glands, thyroid, pancreas, prostate, and urinary and gall bladders (29). 11q13 chromosome amplification and subsequent Ano1 overexpression are indicators of poor prognosis for a variety of tumors (1,19,27,40).…”
mentioning
confidence: 99%
“…On the other hand, in MASC, some authors also found luminal ACC acinic cell carcinoma expression of DOG1 but unlike ACC, such expression was limited to a few areas [13,26]. In general, DOG1 has been studied on two aspects: (a) as a marker with membranous pattern of expression that helps the diagnosis of certain tumors (such as gastrointestinal stromal tumors) and (b) the relationship of its channel function with tumorigenesis as well as with proliferation, migration, and apoptosis resistance of cancer cells [27][28][29]. In salivary tumors, DOG1 has only been analyzed in relation to its utility as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…ANO1 also behaved similarly in cancer cells or tissues, playing different roles in proliferation in different cancer cell types, e.g., ANO1 promotes cell proliferation in many cancer tissues [7] but in one liver cancer cell line it could dramatically prohibit cell proliferation (data not shown).…”
Section: Ano1 Located To Different Vessel Beds May Play Different Rolmentioning
confidence: 97%
“…Since the endogenous CaCC channelsin mammals were identified as the products expressed by ANO1 (anoctamin1) or TMEM16A (transmembrane member 16a) gene in 2008 [4][5][6] , major progresses have been made in the study of various aspects of CaCC-mediated physiological functions and phenomena in mammals [1][2][3]7] . Among the progresses, the channel identification outstandingly contributes to the elucidation of its roles in vascular functions [3,8] .…”
Section: Camentioning
confidence: 99%
See 1 more Smart Citation